Information Technology Support and Accounting Digitalization on Business Development Potential with Knowledge Management as an Intervening Variable in Micro, Small and Medium Enterprises in Deli Serdang Regency - Fadhila, Zakia; Mahyudin, Mahyudin (CV. Rayyan Dwi Bharata, 2024)
There are still relatively many MSMEs in the Deli Serdang district area that have not used technology as a medium to assist in increasing their business where in this day and age technology plays a very important role in increasing sales to the international scope. The Deli Serdang district government, which cares about increasing MSMEs, makes socialization for business actors within the Cooperative and SMEs Office to be given training in the use of business digitalization in order to provide an understanding that digitalization is the right way in this day and age to manage businesses both in production, marketing, finance and management. This research will be conducted in the Deli Serdang district with a population of MSMEs that already have NIB of 570 businesses with a sampling method using the Slovin formula with an error rate of 5%, so that a research sample of 235 can be found. Directly the information technology support variable has a significant effect on kenowlodge management. Directly the information technology support variable has a significant effect on the business development potential of the business, directly the accounting digitalization variable has a significant effect on kenowlodge management, directly the accounting digitalization variable has a significant effect on business development potential, directly the knowledge management variable has a significant effect on business development potential, indirectly the Knowledge Management variable has a significant role in mediating Information Technology support on Business Development Potential, indirectly knowledge management does not have a significant role in mediating accounting digitalization support on Business Development Potential